The Feasibility and Effectiveness of a Physics Enrichment Book Based on Ethnophysics of the Borobudur Temple - Raden Rohadi; Supriyadi; Ani Rusilowati (Universitas Negeri Semarang, 2025)
This study aims to explore ethnophysical concepts embedded in Borobudur Temple and to develop a contextual physics enrichment book for senior high school students. Indonesia possesses a rich cultural heritage with strong potential for contextualized science education, and Borobudur Temple—an architectural masterpiece that embodies various physics principles—offers a unique opportunity to design culturally relevant learning resources. The research employed a Research and Development (R&D) approach using the AM3PU3 model and a one-group pretest–posttest design involving 74 students from SMA Negeri 1 Tengaran. Data were collected through expert validation, student questionnaires, and pretest–posttest scores, and analyzed using the N-Gain test. The findings indicate that mechanical concepts grounded in ethnophysics are present in the temple’s structure and can support culturally based physics instruction. The developed book received expert validation scores of 3.40 for content, 3.83 for language, and 3.63 for presentation (on a 1–4 scale). Student responses were also high, with scores of 4.00 for readability, 3.98 for effectiveness, and 3.90 for design (on a 1–5 Likert scale). The N-Gain result of 0.30 indicated a moderate improvement. These findings suggest that integrating ethnophysics may serve as a culturally responsive strategy to enhance students’ conceptual understanding and engagement in science education.